Anaerobic speed reserve: A key component of elite male 800-m running - Sandford, G. N.; Allen, S. V.; Kilding, A. E.; Ross, A.; Laursen, P. B. (International Journal of Sports Physiology and Performance, 2019)
Purpose: In recent years (2011-2016), men's 800-m championship running performances have required greater speed than previous eras (2000-2009). The "anaerobic speed reserve" (ASR) may be a key differentiator of this performance, but profiles of elite 800-m runners and their relationship to performance time have yet to be determined. Methods: The ASR-determined as the difference between maximal sprint speed (MSS) and predicted maximal aerobic speed (MAS)-of 19 elite 800- and 1500-m runners was assessed using 50-m sprint and 1500-m race performance times. Profiles of 3 athlete subgroups were examined using cluster analysis and the speed reserve ratio (SRR), defined as MSS/MAS. Results: For the same MAS, MSS and ASR showed very large negative (both r = -.74 ± .30, ±90% confidence limits; very likely) relationships with 800-m performance time. In contrast, for the same MSS, ASR and MAS had small negative relationships (both r = -.16 ± .54; possibly) with 800-m performance. ASR, 800-m personal best, and SRR best defined the 3 subgroups along a continuum of 800-m runners, with SRR values as follows: 400-800 m = 1.58, 800 m = 1.57 to = 1.48, and 800-1500 m = 1.47 to = 1.36. Conclusion: MSS had the strongest relationship with 800-m performance, whereby for the same MSS, MAS and ASR showed only small relationships to differences in 800-m time. Furthermore, the findings support the coaching observation of three 800-m subgroups, with the SRR potentially representing a useful and practical tool for identifying an athlete's 800-m profile. Future investigations should consider the SRR framework and its application for individualized training approaches in this event.